2023
DOI: 10.1186/s13148-023-01478-w
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetically regulated gene expression profiles decipher four molecular subtypes with prognostic and therapeutic implications in gastric cancer

Abstract: Background Gastric cancer (GC) is one of the most common malignant tumors of the digestive tract which seriously endangers the health of human beings worldwide. Transcriptomic deregulation by epigenetic mechanisms plays a crucial role in the heterogeneous progression of GC. This study aimed to investigate the impact of epigenetically regulated genes on the prognosis, immune microenvironment, and potential treatment of GC. Results Under the premise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…However, rational application of these classifications in clinical settings is still not widespread, mainly due to their intricacy. Beyond these studies, many researchers have sought other surrogate molecular classifications of GC to detect biomarkers and validate therapeutic prediction based on various analyses, including epigenome, proteome, metabolome, immunity, and tumor mutational burden [ 56 , 72 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. However, no studies can be said to have succeeded in identifying alternative markers that allow more efficient categories than those of TCGA and ACRG.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…However, rational application of these classifications in clinical settings is still not widespread, mainly due to their intricacy. Beyond these studies, many researchers have sought other surrogate molecular classifications of GC to detect biomarkers and validate therapeutic prediction based on various analyses, including epigenome, proteome, metabolome, immunity, and tumor mutational burden [ 56 , 72 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. However, no studies can be said to have succeeded in identifying alternative markers that allow more efficient categories than those of TCGA and ACRG.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“… Weng’s classification. Clinicopathological and molecular features of GC types [ 172 ]. MSI: microsatellite instability; CIMP: CpG island methylator phenotype.…”
Section: Figurementioning
confidence: 99%
“…The C3 type was the least sensitive to gefitinib, gemcitabine, and sorafenib. [172] In their investigation, Weng et al analyzed data from 1521 GC samples across five independent datasets from GEO and TCGA databases [172]. Utilizing an integrated clustering algorithm that combined miRNA expression and DNA methylation profiles, they identified four distinct molecular types of GC, subsequently validated into four independent multicenter cohorts as follows: cluster 1 (C1, 30.4%), C2 (22.7%), C3 (15%), and C4 (32%).…”
Section: Wei Et Al (2022): Tumor Mutational Burdenmentioning
confidence: 99%
“…In contrast, the C4 cluster involves immune-related processes, microsatellite stability, and TP53 mutations and relates to high-grade carcinomas and poor prognosis. Clusters 2 and 3 seem to correlate to a moderate prognosis, and advanced stages and are related to histone and DNA alterations, signaling pathways and immune invasion [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond TCGA and ACRG classifications, several other classifications have been proposed. Recently, Weng et al (2023) suggested an epigenetic-based classification. According to their proposal, the analysis of 1521 GC cases from GEO and TCGA databases in combination with miRNA-expression and DNA-methylation profiles led to four molecular GC clusters.…”
Section: Introductionmentioning
confidence: 99%